Acquired immune deficiency syndrome (AIDS) and late presentation in Poland – data from Test and Keep in Care (TAK) Polska project. Issue 5 (6th January 2021) - Jabłonowska, E; Szetela, B; Bielecki, M; Horban, A; Bociąga‐Jasik, M; Mularska, E; Hlebowicz, M; Olczak, A; Parczewski, M; Grzeszczuk, A; Bielec, D; Cybula, A; et al.
Abstract : Objectives: Late presentation (LP) at HIV diagnosis is associated with worse prognosis and an increase in the number of new infections. We analyse the proportion of patients diagnosed late and factors related to LP in Poland in 2016–2017. Methods: Data were obtained from 13 out of 17 HIV centres in Poland from 2016 and 2017, including date of diagnosis, age, sex, transmission route, anti‐hepatitis C virus (anti‐HCV), Venereal Diseases Research Laboratory (VDRL) antibodies, AIDS diagnosis, baseline HIV viral load and CD4 count. Results: Out of 1522 patients, 88.9% were male with median age of 33.6 years. Men who have sex with men (MSM) comprised 69.4% of all new infections, heterosexual route of transmission (HTX) 18.2% and injecting drug use (IDU) 4.7%. Late presenters comprised 44.8% of the study group. Factors associated with LP were female sex [odds ratio (OR) = 1.5, 95% confidence interval (95% CI): 1.09–2.08], older age (OR = 1.59, 95% CI: 1.42–1.79 per decade), route of transmission (HTX: OR = 1.96, 95% CI: 1.50–2.56; IDU: OR = 3.17, 95% CI: 1.92–5.37), positive HCV results (OR = 1.90, 95% CI: 1.23–2.95) and syphilis diagnosis (OR = 2.06, 95% CI: 2.29–3.31). Adjusting for these factors, the only independent factors associated with LP were age (OR = 1.52, 95% CI: 1.35–1.71) and route of transmission (HTX: OR = 1.73, 95% CI: 1.23–2.44; IDU: OR = 2.24, 95% CI: 1.25–4.10). Conclusions: Late presentation in Poland follows European trends. A total of 44.8% of all newly diagnosed patients in Poland continue to present late or at the AIDS stage. Independent factors associated with LP/AIDS were older age, IDU and HTX. Patients from these groups should be targeted to improve early diagnosis and medical care.